Frequency reconfigurable patch antenna using liquid metal as switching mechanism. Issue 22 (1st October 2013) - Kelley, M.; Koo, C.; McQuilken, H.; Lawrence, B.; Li, S.; Han, A.; Huff, G.
Abstract : The use of liquid metal as a switching mechanism for a frequency‐reconfigurable edge‐fed microstrip patch antenna designed to operate in either the 2.4 GHz ISM band or the 1.6 GHz GPS band is illustrated. A partitioned fluidic manifold bonded to the top of the antenna enables the pressure‐driven displacement of a low‐loss dielectric fluid and the liquid metal from a reservoir atop the patch to switch between the two antenna states. Fabrication and measurement of the antenna illustrates the use of fluidics as an alternative to RF switches for reconfigurable antennas.